Microstructures and mechanical properties of CrMnFeCoNi high entropy alloys fabricated using laser metal deposition technique - Xiang, Shuo; Luan, Hengwei; Wu, Jian; Yao, Ke-Fu; Li, Jinfeng; Liu, Xue; Tian, Yanzhong; Mao, Wenlue; Bai, Hua; Le, Guomin; Li, Qiang (Journal of alloys and compounds, 2019)
In this paper, a laser metal deposition (LMD) process has been applied to the fabrications of CrMnFeCoNi high entropy alloys. The microstructures and mechanical properties of the CrMnFeCoNi alloys prepared using casting technique and LMD technique have been investigated. It has been found that the CrMnFeCoNi samples prepared using casting show a coarse dendritic structure. The microstructures of LMD samples contain both columnar grains and/or equiaxed grains, and the proportion of columnar grains and equiaxed grains can be adjusted by changing the laser power. Besides, the mechanical properties of LMD samples can be adjusted by changing laser power, due to columnar to equiaxed transitions (CET) that are effected by solidification mode and the heat flux direction of LMD process. It is worth to mention that the mechanical properties of the 1400 W samples produced using LMD are better than those produced by casting, which is rarely observed. Furthermore, CrMnFeCoNi alloys prepared using LMD show excellent mechanical properties at cryogenic temperatures. •The microstructures of LMD high entropy alloy can be adjusted by changing the LMD laser power.•The both strength and ductility of LMD high entropy alloy increase as temperature decreases.•The mechanical properties of LMD samples are better than those of as-cast samples.